1999
DOI: 10.1080/09629359990423
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Decreases Human Macrophage Interleukin‐6 Synthesis at Post‐Transcriptional Level

Abstract: In addition to its well-established effect on T cells, cyclosporin A (CsA) also inhibits inflammatory cytokine production by macrophages. However, little is known about the mechanism of action of CsA on macrophage cytokine production. We measured the effect of CsA on basal and phorbol-myristate-acetate (PMA)-stimulated production of interleukin-6 using the human monocyte cell line U937 differentiated with dimethylsulfoxide (DMSO). Interleukin-6 levels were measured in supernatant and cell lysates using specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The resulting delay in removing cell debris after injury may result in the deposition of calcium, which hampers subsequent phagocytosis. Although the evidence concerning CsA effects on macrophages is not always consistent (for a review, see Losa Garcia et al 1996), observations such as the inhibition of macrophage activation and of cytokine production by these cells and the reduced phagocytosis (see, for example, Thorat et al 1994;Holschermann et al 1996;Wasaki et al 1997;Garcia et al 1999) support our speculation.…”
Section: Influences On Muscle Regenerationsupporting
confidence: 62%
“…The resulting delay in removing cell debris after injury may result in the deposition of calcium, which hampers subsequent phagocytosis. Although the evidence concerning CsA effects on macrophages is not always consistent (for a review, see Losa Garcia et al 1996), observations such as the inhibition of macrophage activation and of cytokine production by these cells and the reduced phagocytosis (see, for example, Thorat et al 1994;Holschermann et al 1996;Wasaki et al 1997;Garcia et al 1999) support our speculation.…”
Section: Influences On Muscle Regenerationsupporting
confidence: 62%
“…It reduces the activity of the immune system by interfering with the activity and growth of T cells (5). Previous reports show that CsA decreased IL-6 synthesis at the post-transcriptional level in human macrophages (6). In addition, previous studies have shown that CsA treatment reduces inflammation by down-regulating production of several inflammatory cytokines (6–8).…”
Section: Introductionmentioning
confidence: 82%
“…IL-6 levels are reduced by steroids 49,50 and cyclosporine. 51 Immunosuppressed low IL-6 producers may have very low IL-6 levels and, paradoxically, may be more prone to vascular injury.…”
Section: Discussionmentioning
confidence: 98%